Kemanjuran Beberapa Ekstrak Pestisida Nabati Terhadap Hama Wereng Coklat (Nilaparvata lugens Stall) - Saniah Saniah; Samharinto Samharinto; Nofia Hardarani (Agroekotek View, 2019)
Planthopper pests are very harmful rice pests that attack on the vegetative phase. Vegetable pesticide is one of the alternative of brown planthopper pest control. Vegetable pesticides are relatively easier to make, easier to decompose in nature and safer for humans and the environment. This research used Single Randomized Complete Random Design (RAL) with ten treatment of vegetable pesticide solution type from nine plants, namely: bintaro leaf, galam leaf, kirinyuh leaf, mimba leaf, kepayang leaf, jeruju leaf, sungkai leaf and husk stem . The results showed that all of the vegetable pesticide solution used could cause the death intensity of brown planthoppers more than 80%.